Evaluasi sistem pengendalian internal pada proses pengelolaan dan penyebarluasan data dan informasi geospasial pada badan ABC - Satyarini, Erning Ditta Dyah; Harahap, Siti Nurwahyuningsih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The Geospatial Information Agency, as a government agency, is required to ensure that they have achieved their objectives and carried out their duties and functions; adequate internal control is needed. The internal control system must be able to control operational activities so as to minimize the risks that may occur. The purpose of this study is to evaluate the application of internal control in the process of managing and disseminating geospatial data and information at the Geospatial Information Agency. This research uses the COSO Integrated Internal Control 2013 framework as an internal control evaluation tool. This research only evaluates two components, namely the risk assessment component and the control activity component, along with the principles in them. The research method used is a case study approach through interviews, observations, and document reviews. The result of this study is that ABC Agency has conducted a risk assessment at the operational level but has not conducted a risk assessment at the organizational level. The risk identification that has been done has not considered fraud factors. Control activities have been carried out in accordance with the results of the risk assessment, but there are still controls that are not effective, so additional controls need to be carried out.